Citizenship Education in Secondary Schools in England - Diana Burton; Steph May (Educational Futures, 2015)
Since the introduction of ‘citizenship’ or ‘citizenship education’ (CE) into English schools, its purpose has been widely debated. Is it a subject to be taught, so that citizens learn about our democratic political processes, perhaps as a means of instilling commitment to their nation? Is it a form of training in society’s values, and cultural ethos? Is it an opportunity for community involvement and endeavour? Is it about learning how to be a good or active citizen? These questions persist. This small-scale study seeks to address them by exploring teachers’ experiences of teaching citizenship in secondary schools in the North West of England. We first consider the ideological and political drivers for CE and discuss its various purposes and manifestations. Teacher responses revealed a range of delivery modes in CE, highlighted schools’ inevitable pragmatism in meeting statutory requirements and exposed the need for greater specialist training and a more coherent approach to organising and disseminating resources. The status of the subject within the curriculum and notably its increased cachet if publicly examined, suggest that citizenship education, despite being confirmed as a compulsory subject at Key Stages 3 & 4 within the amended 2014 English National Curriculum, will remain a second tier subject shoehorned into an overcrowded, assessment-driven curriculum.